2019
DOI: 10.1155/2019/6185313
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tissue Penetration of Doxorubicin in Pressurized Intraperitoneal Aerosol Chemotherapy (PIPAC) after High-Intensity Ultrasound (HIUS)

Abstract: Background. High-intensity ultrasound (HIUS) has been studied for the past two decades as a new therapeutic option for solid tumor direct treatment and a method for better chemotherapy delivery and perfusion. is treatment approach has not been tested to our knowledge in peritoneal metastatic therapy, where limited tissue penetration of intraperitoneal chemotherapy has been a main problem. Both liquid instillations and pressurized aerosols are affected by this limitation. is study was performed to evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In addition to temperature, ultrasound also improves the motion and diffusion of molecules. Khosrawipour et al found that, after 300 s of high-intensity ultrasound (HIUS) treatment, tissue penetration of doxorubicin into the peritoneal tissue improved by 3.8-fold (36). Further studies are thus needed to promote the application of I 2 -IK-enhanced micro-CT imaging intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to temperature, ultrasound also improves the motion and diffusion of molecules. Khosrawipour et al found that, after 300 s of high-intensity ultrasound (HIUS) treatment, tissue penetration of doxorubicin into the peritoneal tissue improved by 3.8-fold (36). Further studies are thus needed to promote the application of I 2 -IK-enhanced micro-CT imaging intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know that increasing tissue penetration enhances the antitumor effect with a higher local drug disposition [1]. In previous studies, HIUS has demonstrated substantially enhanced drug penetration in the peritoneal tissue [18]. In the clinical setting, HIUS is increasingly used as a non-invasive treatment for both primary and metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a pressing need to develop methods with improved drug delivery resulting in increased drug penetration depths. Preliminary data on high-intensity ultrasound (HIUS) are promising and indicate its potential to increase in-depth tissue penetration of applied substances 18 . While the addition of HIUS results in a threefold increased drug penetration compared to conventional IPC without HIUS, the feasibility of its application within the abdominal cavity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…HIUS could also activate the particles itself to interact with the surrounding surface and release their chemical compounds as recently shown [13]. e possibility of using HIUS to improve drug penetration of fluid chemotherapy has already been demonstrated [22].…”
Section: Discussionmentioning
confidence: 99%
“…HIUS could also activate the particles itself to interact with the surrounding surface and release their chemical compounds as recently shown [ 13 ]. The possibility of using HIUS to improve drug penetration of fluid chemotherapy has already been demonstrated [ 22 ]. This effect is supposedly attributed to the morphological changes on the peritoneal surface and on the underlying tissue by HIUS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%